Genetic polymorphisms of CYP3A4: CYP3A4⁎18 allele is found in five healthy Malaysian subjects - Ruzilawati, A.B.; Suhaimi, A.W. Mohd; Gan, S.H. (Clinica chimica acta, 2007)
Cytochrome P450 3A4 (CYP3A4) is the major cytochrome involved in metabolizing of >60% of all drugs used in humans. A number of allelic variations in CYP3A4 gene are known to affect catalytic activity including CYP3A4⁎4, CYP3A4⁎5 and CYP3A4⁎18. We investigated the frequencies of CYP3A4⁎4, CYP3A4⁎5 and CYP3A4⁎18 alleles in a Malaysian population. This will impact treatment of patients receiving drugs metabolized by these alleles. The study was conducted in 121 healthy Malaysian volunteers. DNA was extracted from leucocytes and the 3 alleles were determined by PCR–RFLP. The PCR product was later digested with restriction enzymes BstMA I, BshV I and Hpa II. No mutations were detected for CYP3A4⁎4 and CYP3A4⁎5 alleles. The frequency of the CYP3A4⁎18 allele in the Malaysian population is 2.1%. All 5 subjects with CYP3A4⁎18 mutations were found to be heterozygous. The present study describes polymorphisms of CYP3A4 among Malaysian subjects. Clinical relevance of these genetic variants in these healthy volunteers is under investigation.